Muscular Damage and Kidney Function in Rugby Players after Daily Whole Body Cryostimulation. (12th June 2014) - Lombardi, Giovanni; Colombini, Alessandra; Porcelli, Simone; Mauri, Clara; Zani, Viviana; Bonomi, Felice; Melegati, Gianluca; Banfi, Giuseppe
Abstract : Muscular damage, consequent to strenuous activities, could exceed the recovery potential of muscles and determine renal failure. Whole body cryostimulation is a cold-based therapy used to improve recovery or overcome fatigue symptoms. This study aimed to evaluate the effects of repeated sessions of cryostimulation on muscle damage, renal function, and their relationship. Serum samples, from 27 elite rugby players, under training, before and after 2 sessions/day of cryotherapy over 7 days, were tested for markers of muscular (creatine kinase, lactate dehydrogenase, and aspartate aminotransferase) and renal (creatinine, cystatin C) functions. eGFR was calculated with two formulas based on either serum creatinine concentration (MDRD) or serum creatinine and cystatin C concentrations (creatinine/cystatin C CKD EPI). Pre- and posttreatment differences were determined by Wilcoxon's test; correlations were evaluated with Spearman's test. Cryostimulation helped muscular recovery (increased lactate dehydrogenase activity( P < 0.001 ) and the stabile creatine kinase and aspartate aminotransferase activities). Creatinine was unaffected while cystatin C was increased( P = 0.013 ) . Creatinine-based eGFR was not affected by cryostimulation, while creatinine/cystatin C-based eGFR showed a slight decrease( P = 0.015 ) . eGFR and muscular biomarkers were not correlated, suggesting a real recovery effect of cryotherapy. Cystatin C seemed more sensible than creatinine in evaluating the kidney function.